Fertility Decline in Nicaragua 1980-2006 : A Case Study - World Bank (World Bank, Washington, DC, 2017)
Nicaragua, a largely urban country (56 percent of the population lives in urban areas), is one of the least populous (5.53 million) and poorest countries in CentralAmerica. Following reforms in the 1980s, Nicaragua made remarkable progress in gender equity in education and the labor force, while the wide availability of primary health care initiated in the 1970's, including family planning services, led to improvements in infant and child mortality rates. Several lessons emerge from Nicaragua's success at reducing fertility. The government was committed to gender equity and female empowerment through educating girls and women and recruiting women into the labor force. Family planning services were provided within a well functioning primary health care system, including an extensive, efficient contraceptive distribution network that works with international donors, and international and national Non-Governmental Organizations (NGOs) to offer women a good mix of options. Demand must be created through a timely public education campaign. Success requires civic engagement with stakeholders, which may initially mean avoiding unnecessary confrontation and publicity of services for addressing the concerns of more conservative stakeholders.